2010
DOI: 10.1371/journal.pone.0011980
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Signaling in Mouse Taste Buds

Abstract: BackgroundThe neuropeptide, oxytocin (OXT), acts on brain circuits to inhibit food intake. Mutant mice lacking OXT (OXT knockout) overconsume salty and sweet (i.e. sucrose, saccharin) solutions. We asked if OXT might also act on taste buds via its receptor, OXTR.Methodology/Principal FindingsUsing RT-PCR, we detected the expression of OXTR in taste buds throughout the oral cavity, but not in adjacent non-taste lingual epithelium. By immunostaining tissues from OXTR-YFP knock-in mice, we found that OXTR is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…The plasma [OXT] for mice injected with vehicle only was ∼0.1 nM, with a range of 0.01 to 0.49 nM, similar to the 0.02 to 0.1 nM value reported in other rodent studies [38, 40, 41]. On the other hand, the EC 50 for central OXT-responsive neurons is ∼22 nM and ∼33 nM for OXT-responsive taste cells [26, 41]. Thus, we selected an i.p.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The plasma [OXT] for mice injected with vehicle only was ∼0.1 nM, with a range of 0.01 to 0.49 nM, similar to the 0.02 to 0.1 nM value reported in other rodent studies [38, 40, 41]. On the other hand, the EC 50 for central OXT-responsive neurons is ∼22 nM and ∼33 nM for OXT-responsive taste cells [26, 41]. Thus, we selected an i.p.…”
Section: Resultssupporting
confidence: 80%
“…We previously reported that OXT receptor is expressed in a subset of murine taste bud cells and that OXT elicits calcium responses from those same cells [26]. Other investigators have shown OXT receptor expression (and OXT-elicited calcium responses) in a cell line derived from human fungiform papillae [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hormones that bind to receptors on taste cells alter the palatability of food and, therefore, intake. Current knowledge of the hormonal modulation of taste function is summarized in Table 1 [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] and described in greater detail below.…”
Section: Hormonal Modulation Of Taste Functionmentioning
confidence: 99%
“…The oxytocin receptor, on the other hand, was found on type I taste cells. 72 Oxytocin is presumed to act as an endocrine hormone on taste buds by influencing type I cells and consequently the structure of the taste bud. However, mice deficient in the oxytocin receptor did not show any morphological alterations.…”
Section: Oxytocinmentioning
confidence: 99%
See 1 more Smart Citation